The Assessment of Economic Efficiency of Regulatory Impact on the Crowd Financing Market - Kuvaeva U.V.; Chudinovskikh M.V.; Boronenkova N.L.; Sergienko A. N. (SHS Web of Conferences, 2021)
In the last few years, conditions have been created in the world economy that contribute to the active crowdfunding market development, through which the so-called «alternative financing» is implemented. The paper describes the transformation of crowdfunding model types, emphasizes the importance of regulatory impact on the specified market. The general procedure for regulatory impact assessments (RIA), developed and recommended by the OECD based on scientific approaches, is considered. The specificity of the approach to RIA in Russia was studied and the conclusion was made about the need to apply RIA to the crowdfunding market, taking into account the improvement of approaches to assessing the costs and benefits of regulation.